Business tourism in Porto from the perspective of local hotels and travel agencies - Haghgou, Elaheh; Pataco, Teresa; Liberato, Dália (E- Revista de Estudos Interculturais, 2026)
In recent decades, business travel has become common, helping to organize events and congresses in tourism destinations and sparking the interest of researchers from different scientific areas. Nevertheless, a prevailing challenge in academic research and business tourism is the conceptual development related to the perspective of local hotels and travel agencies on business tourism. This research aims to analyze the profiles and behavioral patterns of business travelers, as perceived by local hotels and travel agencies. It also explores the evolution of business tourism in Portugal, with a particular focus on Porto. The primary goal is to examine the significance of business tourism in Porto for local hotels and travel agencies. To achieve this objective, a qualitative approach methodology is employed, using semi-structured interviews. The main conclusions point to the ideas that were previously researched, while also offering new perspectives